2014
DOI: 10.1016/j.econmod.2014.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-pocket health care expenditure in Turkey: Analysis of the 2003–2008 Household Budget Surveys

Abstract: This paper analyses the prevalence of 'catastrophic' out-of-pocket health expenditure in Turkey and identifies the factors which are associated with its risk using the Turkish Household Budget Surveys from 2002 to 2008. A sample selection approach based on Sartori (2003) is adopted to allow for the potential selection problem which may arise if poor households choose not to seek health care due to concerns regarding its affordability. The results suggest that poor households are less likely to seek health care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 15 publications
2
36
0
3
Order By: Relevance
“…The results overall are consistent with the study by Brown et al (2014); however, our analysis is expanded examining all the health insurance types, including the accessibility to health centers and transportation, wealth, as well as, the DID approach will be applied in order to see the effectiveness of the health reform of 2008. However, these estimates are not based on propensity score matching; thus it is highly possible that there is selection bias and heterogeneity in the sample.…”
Section: Health Insurance Types and Determinants Of Oopectp And Catassupporting
confidence: 80%
See 1 more Smart Citation
“…The results overall are consistent with the study by Brown et al (2014); however, our analysis is expanded examining all the health insurance types, including the accessibility to health centers and transportation, wealth, as well as, the DID approach will be applied in order to see the effectiveness of the health reform of 2008. However, these estimates are not based on propensity score matching; thus it is highly possible that there is selection bias and heterogeneity in the sample.…”
Section: Health Insurance Types and Determinants Of Oopectp And Catassupporting
confidence: 80%
“…Following the previous literature (Van Doorslaer et al, 2007;Mugisha et al, 2007;Barros and Bertoldi, 2008;Erus and Aktakke, 2012;Brown et al, 2014) the regressions control for various individual and household characteristics, including gender, age, education level, household income, marital and job status, occupation industry code, rural versus urban area, years of working, years of leaving in the current residence, difficulties in access to transportation points and health centers and year. These controls are useful, since education, job status, years of work and household income may cause the decision and the type of health insurance.…”
Section: Datamentioning
confidence: 99%
“…This is because poor households are less likely to seek health care and hence incur less catastrophic health expenses compared to non-poor households. In addition, OOP made by higher income groups are usually directed towards buying private health insurance to afford extra private hospital costs that are not paid by SSI [84]. Overall, our review suggests that a regressive OOP characteristic persisted even after the reforms.…”
Section: Equitymentioning
confidence: 81%
“…They interpreted these effects as a positive impact of the Health Transformation Programme. Brown et al [25] examined the presence of catastrophic out-of-pocket health expenditures in Turkey and found the crucial factors which had an impact on it by using the Turkish Household Budget Surveys for the 2003-2008 period. According to the different cut-off point of expenditure, they indicated that between 16% and 18% of households spent more than 2.5% of their income on healthcare, and between 1% and 2% of households spent more than 20% of their total expenditure for the 2003-2008 period.…”
Section: Related Workmentioning
confidence: 99%